INFLUENCE WORK DISCIPLINE, ORGANIZATIONAL LEARNING, AND MOTIVATION TO EMPLOYEE PERFORMANCE AT PT CIMB NIAGA TBK - Putra, Riduansyah; Ruslan, Sangkala (Dinasti International Journal of Digital Business Management, 2021)
This study aims to measure the effect of work discipline, organizational learning and motivation on employee performance at PT CIMB Niaga Tbk. This research is quantitative. The population is employees of the unsecured credit underwriter group. The sampling technique was using nonrandom sampling, namely saturated samples with a total of 221 employees. The research data were analyzed using multiple linear regression. The results of the t-test for the variables of work discipline, organizational learning, and motivation partially are significant positive on employee performance. The results of the F-test for the variables of work discipline, organizational learning, and motivation simultaneously are significant to employee performance. Suggestions for further research are to include compensation factors as additional independent variables.